Pelatihan Pendesainan Perangkat Pembelajaran yang Melibatkan Literasi Matematika untuk Guru Sekolah Menengah - Tria Gustiningsi; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Rita Inderawati; Elika Kurniadi; Rini Herlina; Chika Rahayu; Lisnani Lisnani; Malalina Malalina; Dewi Rawani; Arika Sari; Delia Septimiranti (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2022)
This activity is carried out with the aim of understanding secondary teachers about learning tools that involve mathematical literacy. The methods used are training, discussion, and mentoring. Training and discussions were carried out using zoom for two days, while mentoring was carried out using google classroom for one month. The target of this activity is secondary teachers in Pagaralam City, South Sumatera. Evaluation is carried out by giving assignments to teacher and providing a satisfaction questionnaire for implementation. The results show that teachers are satisfied with the overall implementation of the activity and teachers understand learning tools that involve mathematical literacy, teachers can design tools well and test them out on students.